Plang Edukasi Berapa Lama Sampah Terurai - Palta, Marsel Deno; Insagi, Eep Elpres; Anugrah, Jovandika; Pranata, Aldi; Imran, Ranny Fitri; Karmanita , Deti; Susena, Karona Cahya (Jurnal Kewirausahaan dan Bisnis, 2026)
Household waste remains a major problem in residential areas, including RT 03 RW 01, Penurunan Village, Ratu Samban District, Bengkulu City. Low public awareness of sorting and disposing of waste according to type has resulted in an unclean environment and the potential for pollution. One effort that can be made to overcome this problem is through the installation of waste education signs. Waste education signs serve as a medium of information and a reminder for residents to dispose of and sort waste properly. This activity aims to increase public awareness of the importance of waste management starting from the household level and to create a clean, healthy, and sustainable environment.